THEORETICAL PRINCIPLES OF ENTERPRISE MANAGEMENT IN A CRISIS - Repushevska , Yu.O. (The actual problems of regional economy development, 2018)
Structural transformations in the Ukrainian economy are accompanied by changes in the mechanisms of cooperation between business entities of all forms of ownership, both between themselves and the state. One of the directions of the regulation of relations is the formation of a system of crisis management, which sets qualitatively new directions of coordination of goals and interests of organizational and legal structures that still can not adapt to the harsh environment conditions. The article is aimed at the improvement of theoretical and methodological principles for the formation of crisis management decisions and the development of scientific and practical recommendations on improving the efficiency of enterprise management in a crisis. Insufficient solving of tasks regarding the definition and implementation of crisis-based transformations at enterprises with a view to their restructuring from the point of view of restoration and preservation of capital-creating function, led to the choice of research topic. We were tasked with a set of restructuring measures that ensure the stabilization of the company's activities on the basis of a generalization of the theoretical principles of enterprise management in a crisis. Conducted analysis of the concept of "crisis" and "bankruptcy" of enterprises. Proposed author definition of the concept of "restructuring".